PERANCANGAN ROBOT FOLLOWER MENGGUNAKAN HISTOGRAM MATCHING DAN PYRAMID SEARCHING - Yapriady Yapriady (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
In this project, the robot have ability to detect the movement of object using the camera. The first process is tracking by search in part of image captured by the camera. Each frame will be compared with a pixel matrix of the object of interest. Searching process is started from the middle of the image captured by the camera then is continued into matrix of pixels in other areas using Pyramid Searching method. We use Histogram Matching method to compare between matrix of pixels. The Direction of moving object’s information will be sent to the microcontroller to move the robot. Key words Histogram Matching, Pyramid Searching, Robot Follower